I riti quotidiani connessi al caffè nel romanzo di Widad Tamimi Il caffè delle donne - Kłosek, Wiesława (Romanica Silesiana)
Martine Segalen, French ethnologist, pondering over rituals in lives of individuals and societies which are technology oriented, points not to the de‑ritualization but to change of the plane on which rituals occur (a shift from center to margin). Repeated everyday actions always become rituals when they carry symbolic meanings. According to Stewart Lee Allen, drinking coffee together is one of the most prevalent social rituals. For ages coffee was called a ‘devilish beverage’; on the other hand, it was used in religious rituals as a means of contact with God. For Qamar, the protagonist of Widad Tamimi’s novel Il caffè delle donne, drinking coffee becomes a ritual which was analyzed on the three levels: collective, individual and intimate relationship. The main point of the novel is coffee taseography, a mantic technique; it can be traced to the beginnings of Arabic traditions. For Qamar, of Arab origin, coffee not only becomes a ritual of initiation, but also is a stimulus for her new identity to emerge. An everyday cup of coffee shows a process of changes she undergoes, and helps her in solving her identity crisis. It appears that one of the keys to reading Widad Tamimi’s novel is a meaning of rituals for immigrants who must find themselves in the new social environment and determine their new identity. Key words: daily rituals, Italian migration literature, coffee tasseography, meaning of a ritual in the migration context, identity crisis